A INFLUÊNCIA DO AMBIENTE FAMILIAR NA MANIFESTAÇÃO DO TRANSTORNO DE PERSONALIDADE NARCISISTA - Oliveira, Heloísa de Lima; Amorim, Aline Maria de Melo; Gama , Keit Maciel da; Silva, Olavo Wesley Alves Torres da; D’Almeida, Karis Tarita Batista Alexandre; Lopes, Gustavo Rodrigues; Rocha , Fábio José da; Diógenes , Kayky Eduardo Perdiz; Cunha, Leilane Lira da; Lobo, Stephanie Suzano; Santos, Thiago Ferreira dos; Aurélio, Salete Martens (Brazilian Journal of Implantology and Health Sciences, 2024)
The manifestation of Narcissistic Personality Disorder (NPD) is often influenced by various factors, with the family environment being an important component. Family dynamics play a crucial role in the development of this disorder, impacting the formation of the individual’s self-image and patterns of interpersonal relationships. In this context, understanding the influence of the family environment on the expression of NPD is fundamental to effectively address this complex psychological condition. Objectives: To investigate and understand the specific influence of the family environment on the manifestation of narcissistic personality disorder, exploring interaction patterns, parental styles, and family dynamics that may contribute to the development of this disorder. Methodology: Articles found were read, and inclusion and exclusion criteria were applied. Within the inclusion criteria, original articles addressing the investigated topic and allowing full access to the study’s content were considered, published between 2016 and 2023, in Portuguese and English. The research was conducted through online access to the databases of the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Health Sciences Literature (LILACS) in February 2024. Results and Discussions: The complexity of treating narcissistic personality disorder (NPD) is highlighted. Psychopharmacological treatments have shown limited efficacy, being more useful in comorbidities with other conditions. Several psychotherapeutic approaches were explored, with Dialectical Behavioral Therapy and Schema-Focused Therapy standing out, as well as psychoanalytic approaches such as Transfer-Centered Psychotherapy and Mentalization-Based Therapy. However, regardless of the approach, narcissistic patients are challenging to treat due to difficulty in accepting the diagnosis and lack of empathy. Motivation for change often arises from external crises, making therapeutic commitment fragile. Therapists’ countertransference is also a challenge, with difficult-to-manage negative feelings that, when understood, can provide valuable information about the patient’s internal world. In summary, the results highlight the need for therapeutic strategies adapted to the complexity of NPD, considering the specific characteristics of narcissistic patients and the inherent challenges in the therapeutic process. Conclusion: In conclusion, addressing Narcissistic Personality Disorder (NPD) demands a deep understanding of therapeutic nuances. The results underscore the complexity in the effectiveness of psychopharmacological treatments and the importance of specific psychotherapeutic approaches. Difficulty in accepting the diagnosis, lack of empathy, and challenges in countertransference emphasize the need for adapted therapeutic strategies. Amidst these challenges, the pursuit of realistic treatment goals and the creation of therapeutic contracts are crucial. These findings underline the importance of continuing research and refining therapeutic approaches to effectively manage NPD.